Prokaryotic and Eukaryotic DNA in Prevention and Treatment of Infectious Diseases - N. N. Besednova; I. D. Makarenkova; L. N. Fedyanina; ZH. I. Avdeeva; S. P. Kryzshanovsky; T. A. Kuznetsova; T. S. Zaporozhets (Антибиотики и Химиотерапия)
The review article presents the materials of recent years dedicated to the analysis of modern data about the possible aspects of the use of deoxyribonucleic acid (DNA) and oligodesoxinucleotides (natural and synthetic) from pro - and eukaryotes for the prevention and treatment of infectious diseases.The authors focus on bacterial DNA with a high content of CpG motifs, as well as on unmethylated CpG oligonucleotides (CpG-ODN), which stimulate the system of innate and adaptive immunity. Due to the absence of pronounced toxicity and good tolerance of the macroorganism, these compounds are of great interest for medical use, in particular as adjuvants. At the same time, the authors note the need to develop effective CpG-ODN delivery systems in tissues and target cells.With respect to CpG-motives of eukaryotic DNA, the possibility of their use as a basis for effective adjuvants, immunomodulators, antiviral and antibacterial compounds is considered.